ANALISIS KEBIJAKAN PENDIDIKAN TENTANG SISTEM INFORMASI MANAJEMEN - Sainuddin, Moh Rizal; Semi, Hijar; Yuspiani; Naro, Wahyuddin (Department of Islamic Education Management, 2024)
This study aims to determine the Analysis of Education Policy on Management Information Systems. The research method used is qualitative research, with data from articles, journals, and relevant experiences. The discussion of this research includes Education Policy Analysis, SIM, characteristics, components, objectives, and implementation. The conclusion in this study is that, Education Policy Analysis focuses on efficiency and effectiveness, including normative, structural, constituent, and technical dimensions. Education Management Information System (SIM) supports management functions by providing structured information for decision-making. SIM covers various aspects of education management, consisting of human components, procedures, hardware, software and data. Its implementation aims to improve transparency, access to information and the quality of education services, which impacts on the organisation's image.